Tong Sampah dari ban bekas - Satoto, Handy Febri; Hartatik, Nurani (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
This article contains the making of trash cans from used tires. The purpose of this article is to increase public awareness of the implementation of building materials & environmental hygiene and how to Utilize used materials in the neighborhood to be used as a garbage bin. This research is done by direct method of making and questionnaire. From this article can be concluded that the community to utilize the used materials is still lacking. So, there are still many untapped tires. Keywords: trash bin, community, used tires.